Época de sobressemeadura de gramíneas anuais de inverno e de verão no capim-Tifton 85: produção e composição botânica - Moreira, Andreia Luciane; Reis, Ricardo Andrade [UNESP]; Simili, Flavia Fernanda; Pedreira, Marcio dos Santos; Contato, Eduardo Dollo [UNESP]; Ruggieri, Ana Claudia (Universidade Federal de Lavras (UFLA), 2006)
The experiment was conducted at UNESP-Jaboticabal during the 2001-2002 winter-spring-summer periods to evaluate the herbage mass, botanical composition, dry matter production of mix pastures, and leaf: sheat-stem ration of Tifton 85 or overseeding with annual winter or summer species. The treatments were: pearl millet (Pennisetum americanum (L.) Leeke) plus bristeal oat (Avena strigosa Schreb); sorghum sudan grass (Sorghum bicolor (L.) Moench x Sorghum sudanense (Piper) Stapf) (SS AG2501 C) plus bristeal oat, overseeded on Tifton 85 area on 06/19/02/04, or 07/02/02, and Tifton 85, conducted in a randomized block design. The AG2501 contributed with a small participation in the botanical composition and the presence of millet in the experiment was not observed. Highest herbage mass at first and second evaluations related to first seeding time was 63% higher compared to the second seeding time. The herbage mass were similar he production in the other evaluations were similar. on the second seeding time, it was observed highest oat species in relation to the first seeding time. The leaf: sheat-stem ration decreased during the experiment due to the pasture botanical composition changes.
Tifton 85 overseeded with cool season forages: Yield and botanical composition
Keywords: Bristeal oat; cool season species; sorghum sudan grass; leaf:sheat-stem ration